2014
DOI: 10.1111/echo.12589
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Region of Interest Width on Two‐Dimensional Speckle Tracking–Based Measurements of Strain and Strain Rate

Abstract: Layer-specific myocardial deformation and curvature dependency lead to an inverse correlation between the chosen ROI width and strain and strain rate measurements. Just one step of ROI-width change leads to a significant bias. Precise ROI-width definition is essential but technical factors limit its feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…[26] As a relatively novel technique, there are still technical challenges for image acquisition. [27] In our study, averaging at least 3 LV segments seems adequate for STE parameters.…”
Section: Discussionmentioning
confidence: 72%
“…[26] As a relatively novel technique, there are still technical challenges for image acquisition. [27] In our study, averaging at least 3 LV segments seems adequate for STE parameters.…”
Section: Discussionmentioning
confidence: 72%
“…The analysis of LV deformation including circumferential strain and rotation may improve the echocardiographic diagnostic approach in AM [ 24 , 27 , 28 ]. However, the use of myocardial deformation is not yet widely implemented in patients with AM [ 36 , 37 ]. Recently, the authors of the present study demonstrated the feasibility to define deformation patterns for radial and circumferential strain as well as rotation in a cohort of healthy volunteers and professional athletes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the authors of the present study demonstrated the feasibility to define deformation patterns for radial and circumferential strain as well as rotation in a cohort of healthy volunteers and professional athletes [ 19 ]. As also performed in the present study, several prerequisites have to be considered during image acquisition and post-processing analyses to exclude artifacts; for example, the acquisition of standardized short-axis views perpendicular to LV long axis, the documentation of apical rotation at the apical third of the left ventricle, the adjustment of the tracking area to exclude paracardial structures, as well as parts of the mitral valve [ 37 ]. Furthermore, the results of rotational deformation need to be counterchecked by multiple documentations to differentiate artifacts from deformation abnormalities as sequelae of SARS-CoV-2-induced myocardial involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized that standard and reference values of deformation imaging should include detailed information about the position and width of the tracking area. Spriestersbach et al reported the influence of ROI width in 20 healthy subjects examined with a Vivid E 7 machine [15]. The Auto ROI applied was derived from a 4-chamber view only, and the endocardial border had been automatically traced based upon markers on the septal and lateral mitral ring and the apex.…”
Section: Discussionmentioning
confidence: 99%